Kesuksesaan Karir Subjektif : Peranan Keseimbangan Kehidupan Keluarga-Kerja dan Komitmen Karir - Fridayanti Fridayanti; Risa Anisa Sholihah; Agus Abdulrahman (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2022)
This study aims to find out the role of work-life balance and career commitment toward the subjective career success of female employees. Participants of this study were 52 female employees in a state-owned company (BUMN) in The City of Bandung. The data collection of research was conducted using a subjective career success scale, work-life balance scale, and career commitment scale. The data were analyzed using multiple linear regression analysis. The results of this study showed a significant influence of work-life balance and career commitment on subjective career success. Subsequent findings suggest that work-life balance significantly affects subjective career success. And career commitment is not significant in influencing subjective career success